Эволюция морских экосистем под влиянием вселенцев и искусственной смертности фауны - (:unkn) unknown (My University, 2003)
В сборнике представлены тезисы докладов международной научной конференции, организованной Мурманским морским биологическим институтом КНЦ РАН. Рассмотрены различные аспекты влияния видов-вселенцев и искусственной (в том числе промысловой), смертности фауны на функционирование морских экосистем, а также особенности биологии понто-каспийских видов, вселившихся во внутренние водоемы европейской части России. Обсуждаются вопросы расселения адвентивных видов в новых условиях, проблемы искусственной интродукции гидробионтов и искусственного воспроизводства. Приводятся современные данные по воздействию токсикантов на водные организмы и птиц. Сборник рассчитан на гидробиологов, экологов, фаунистов, специалистов вобласти рыбного хозяйства и охраны природы.
Evolution of marine ecosystems impacted by introducers and artificial mortality of fauna
In the collection of papers there presented abstracts of presentations at the international scientific conference organized by the Murmansk Marine Biological Institute KSC RAS. Different aspects of impact of species introducers and artificial (including fishing) fauna mortality on the marine ecosystems functioning and peculiarities of Ponto- Caspian species biology which settled in the inland water basins of the European part of Russia are discussed. The problems of adventive species resettling in the new conditions, the problems of the artificial introduction of hydrobiontes and artificial restoration are tacked. Current data on the toxic substances impact on aquatic organisms and birds are given. The collection of papers is interesting for specialists in hydrobiology, ecology, fauna investigators, and specialists in marine fishery and nature protection.